Alq mutation increases fruit set rate and allows the maintenance of fruit yield under moderate saline conditions. (22nd July 2019) - Ribelles, Carlos; García-Sogo, Begoña; Yuste-Lisbona, Fernando J; Atarés, Alejandro; Castañeda, Laura; Capel, Carmen; Lozano, Rafael; Moreno, Vicente; Pineda, Benito
Abstract : The enhanced expression of the ALQ-TAGL1 gene in the Alq mutant increases the concentration of endogenous cytokinins, fruit set, and salt tolerance in tomato. Abstract: Arlequin ( Alq ) is a gain-of-function mutant whose most relevant feature is that sepals are able to become fruit-like organs due to the ectopic expression of the ALQ-TAGL1 gene. The role of this gene in tomato fruit ripening was previously demonstrated. To discover new functional roles for ALQ-TAGL1, and most particularly its involvement in the fruit set process, a detailed characterization of Alq yield-related traits was performed. Under standard conditions, the Alq mutant showed a much higher fruit set rate than the wild type. A significant percentage of Alq fruits were seedless. The results showed that pollination-independent fruit set in Alq is due to early transition from flower to fruit. Analysis of endogenous hormones in Alq suggests that increased content of cytokinins and decreased level of abscisic acid may account for precocious fruit set. Comparative expression analysis showed relevant changes of several genes involved in cell division, gibberellin metabolism, and the auxin signalling pathway. Since pollination-independent fruit set may be a very useful strategy for maintaining fruit production under adverse conditions, fruit set and yield in Alq plants under moderate salinity were assessed. Interestingly, Alq mutant plants showed a high yield under saline conditions, similar to that of Alq and the wild type under unstressed conditions.